(untitled) (Conferencea, 2023)
“The possibilities of modern information technologies in the process of learning English” is due to the necessity to use new information technologies and insufficient knowledge of language programs, as well as the growing interest of modern students in multimedia technologies in general. The materials of the work in learning English can help the teacher and students to expand the arsenal of methods and forms of teaching, introduce various types of information technologies in the context of learning English. It may be of interest not only to today’s students, but also to many computer and Internet users who want to expand their language knowledge.